2021
DOI: 10.1159/000516845
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Retardation in Pregnant Women with Long QT Syndrome Treated with Beta-Receptor Blockers

Abstract: Pregnant women with inherited long QT syndrome (iLQTS) are at an increased risk for preterm delivery and intrauterine growth retardation (IUGR) due to their underlying disease. Additionally, they are at a risk of arrhythmogenic events, particularly during the postpartum period because of physiological changes and increased emotional/physical stress. β-receptor blockers can effectively prevent life-threatening Torsades de Pointes ventricular tachycardia and they are the treatment of choice in iLQTS. Use of β-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Gabapentin, lamotrigine, levetiracetam, zonisamide, metoprolol, propranolol, and onabotulinumtoxinA should only be used in pregnant women if the potential benefits outweigh the risks due to the potential for fetal harm in animal studies. [9][10][11][12][13][14][15][16] Pregnancy information is limited with calcitonin gene-related peptide (CGRP) receptor or ligand-directed therapies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Gabapentin, lamotrigine, levetiracetam, zonisamide, metoprolol, propranolol, and onabotulinumtoxinA should only be used in pregnant women if the potential benefits outweigh the risks due to the potential for fetal harm in animal studies. [9][10][11][12][13][14][15][16] Pregnancy information is limited with calcitonin gene-related peptide (CGRP) receptor or ligand-directed therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Atenolol is a Food and Drug Administration category D drug and is currently not recommended in pregnancy due to higher risk of IUGR. 23 Nadolol has been associated with IUGR, 24 neonatal hypoglycemia, and bradycardia, and it should be used for high‐risk patients; 30% of babies born with IUGR were exposed to nadolol in our cohort. There is evidence suggesting that metoprolol is less effective in arrhythmia prevention 25 ; thus, it is not considered as a first‐line BB; bisoprolol is a valuable option in pregnancy, 23 as no IUGR has been reported with its use, 26 although data are limited.…”
Section: Discussionmentioning
confidence: 84%
“…BBs remain the cornerstone of LQTS treatment; however, our study confirms that they can cause lower birth weight compared with untreated women. 24 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…MTP is the fifth most commonly utilized medication in the US, with >75 M yearly prescriptions [ 50 ]. It is often prescribed to pregnant women [ 37 , 39 , 40 , 41 , 42 , 48 , 51 , 52 , 53 , 54 ]. In the preliminary experiments MTP exposure resulted in a 50–100-fold elevation of 7-DHC in neurons and astrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, maternal exposure to medications must be considered to avoid potential adverse effects on the developing fetus. The utilization of antihypertensive drugs during pregnancy, and the potential effect on the developing fetus have been topics of considerable debate: some studies found no negative effect on fetal development [ 39 , 40 ], while others reported increased risk for intrauterine growth restriction, small for gestational age, and preterm delivery [ 41 , 42 , 43 ]. As a result, we embarked on assessing the effects of six commonly used beta-blockers on sterol biosynthesis, utilizing cell lines, neuronal and astroglial cultures, and an in vivo mouse model.…”
Section: Introductionmentioning
confidence: 99%